HUBUNGAN DUKUNGAN SOSIAL ORANG TUA TERHADAP MOTIVASI BELAJAR BAHASA INGGRIS PADA SISWA KELAS VIII DI SMPN 1 CIKUPA - Mega Astarina; Rizki Isfahani; Ayu Pratiwi (Nusantara Hasana Berdikari, 2021)
In the learning process, motivation is so important to achieve the goal. It cannot be separated from the support of parents who are influential in the development and growth of children. Objectives: Knowing the relationship of parental social support to motivation to learn English. This research is quantitative with a descriptive correlational technique with a cross sectional approach. A population of 297 calculated using the Slovin formula obtained 170 samples with random samping technique. Based on Chi-Square analysis, the P Value is 0,047 where if the significance value or P Value <0.05 means Ha is accepted and Ho is rejected, this means that there is a relationship between parental social support and motivation to learn English in class VIII students at SMPN 1 CIKUPA. There is significant relationship between parental social support and motivation to learn English. It is hoped that the result of the study can be taken into consideration in observing the relationship between parental social support and motivation to learn English.